Outcome of real-time telescreening for retinopathy of prematurity using videoconferencing in a community setting in Eastern India - Tapas R Padhi; Souvik Bhunia; Taraprasad Das; Sameer Nayak; Manav Jalan; Suryasnata Rath; Biswajeet Barik; Hasnat Ali; Padmaja Kumari Rani; Dipanwita Routray; Subhadra Jalali (Indian Journal of Ophthalmology, 2024)
Purpose: To evaluate the feasibility and outcome of a real-time retinopathy of prematurity (ROP) telescreening strategy using videoconferencing in a community setting in India. Method: In a prospective study, trained allied ophthalmic personnel obtained the fundus images in the presence of the parents and local childcare providers. Analysis of images and parental counseling were done in real time by an ROP specialist located at a tertiary center using videoconferencing software. A subset of babies was also examined using bedside indirect ophthalmoscopy by an ROP care-trained ophthalmologist. The data were analyzed using descriptive statistics, sensitivity, specificity, positive and negative predictive values, and correlation coefficient. Results: Over 9 months, we examined 576 babies (1152 eyes) in six rural districts of India. The parents accepted the model as they recognized that a remotely located specialist was evaluating all images in real time. The strategy saved the travel time for ROP specialists by 477 h (47.7 working days) and for parents (47,406 h or 1975.25 days), along with the associated travel cost. In a subgroup analysis (100 babies, 200 eyes), the technology had a high sensitivity (97.2%) and negative predictivity value (92.7%). It showed substantial agreement (k = 0.708) with the bedside indirect ophthalmoscopy by ROP specialists with respect to the detection of treatment warranting ROP. Also, the strategy helped train the participants. Conclusion: Real-time ROP telescreening using videoconferencing is sensitive enough to detect treatment warranting ROPs and saves skilled workforce and time. The real-time audiovisual connection allows optimal supervision of imaging, provides excellent training opportunities, and connects ophthalmologists directly with the parents.